AUTOMATIC PORTAL GENERATION FOR 3D AUDIO - FROM TRIANGLE SOUP TO A PORTAL SYSTEM - Turecki, Piotr; Pędzimąż, Tomasz; Pałka, Szymon; Ziółko, Bartosz (Computer Science, 2016)
The purpose of this paper is to investigate an algorithm for generating an automatic portal system. This has been accomplished based on a given set of triangles. The proposed solution was designed to enhance the performance of a sound beam-tracing engine. This solution can also be used for other areas where portal systems are applicable. The provided technical solution emphasizes the beam tracing engine’s requirements. Our approach is based on the work of Haumont et al. (with additional improvements), resulting in improved scene segmentation and lower computational complexity. We examined voxelization techniques and their properties, and have adjusted these to fit the requirements of a beam-tracing engine. As a result of our investigation, a new method for finding portal placement has been developed by adjusting the orientation of the found portals to fit the neighboring scene walls. In addition, we replaced Haumont et al.’s prevoxelization step, which is used for erasing geometrical details (for example, thin walls). This was done by smoothing the distance field that, in effect, eliminated incorrectly positioned portals. The results of our work remove the requirement for walls that separate rooms to have a particular thickness. We also describe a method for building a structure that accelerates real-time queries for determining the area where a given point is located. All of the presented techniques allow for the use of larger sized voxels, which increases performance and reduces memory requirements (not only during the preprocessing phase but also during real-time usage). The proposed solutions were tested using scenarios with scenes of varying complexity.